Platelet-Rich Plasma in Sphincteroplasty - Mohammad Rezazadehkermani (Iranian Journal of Colorectal Research, 2020)
I review the interesting article “Effects of Platelet-Rich Plasma on Healing of Sphincteroplasty: An Experiment in Rabbit Model” (1)about application of Platelet-Rich Plasma in the anal sphincteroplasty While reviewing the article which proposed a novel idea for improving the outcome of sphincteroplasty three issues were questionable for me: The first issue is the site of sphincterotomy as it is mentioned located in posterior midline. It is known that the external anal sphincter is connected posteriorly to the anococcygeal ligament posteriorly (2) and division of sphincter in this point is not always associated with separation of sphincter and fecal incontinence. Animal experiments on the anal sphincter is different in the basis of sphincter function rather than an anatomical basis has a physiologic basis and if sphincterotomy is done in an animal the impaired function should be demonstrated(3) before further intervention. Due to small size of sphincter complex in the small animals it is sometimes hard to understand the exact territory of muscle.